ANALISIS DAMPAK PEMANFAATAN KEBIJAKAN BEA MASUK DITANGGUNG PEMERINTAH (BMDTP) TERHADAP PRODUKTIVITAS SEKTOR INDUSTRI TERTENTU - Hananto Prabowo Hardi Putra (Jurnal Ekonomi dan Pembangunan, 2025)
The non-oil and gas manufacturing sectors in Indonesia still rely on imported raw materials. In order to facilitate firms to enhance its competitiveness through increased productivity, the government issued several policies related to import of industrial raw materials, one of which is Bea Masuk Ditanggung Pemerintah (BMDTP). This study will analyze the impact of the utilization of BMDTP by certain industrial sectors on productivity in those industries. The method used to measure the productivity of those industries is to use total factor productivity (TFP). While the structure of the data used is panel data with unit analysis industrial sector. Thesresults obtained from this study are that BMDTP policyeimplementations have a significant impact on productivity growth of those certain industrial sectors.